Incubator Analyzer Using Bluetooth Android Display (Humidity & Air Flow) - Vina Nadhirotul Azkiyak; Syaifudin Syaifudin; Dyah Titisari (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2019)
Abstract— Incubator Analyzer is a calibrator used to calibrate incubator temperature, mattress temperature, noise, humidity and airflow so that conditions in the baby incubator environment remain stable and within normal limits. The purpose of this study is to develop a system for sending data to android and data storage.